2020
DOI: 10.1177/2164956120973983
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a University-Wide Interdisciplinary Mind-Body Skills Program on Student Mental and Emotional Well-Being

Abstract: Background Positive effects of mind-body skills programs on participant well-being have been reported in health professions students. The success seen with medical students at this university led to great interest in expanding the mind-body skills program so students in other disciplines could benefit from the program. Objective The purpose of this study was to assess the effects of a 9-week mind-body skills program on the mental and emotional well-being of multidisciplinary students compared to controls. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Consistent with the present results, a short-term increase in resilience was found among forty-four participants who engaged in six weekly mind-body intervention sessions [ 34 ]. Similarly, a study found that after engaging in a 9 week mind-body intervention, 279 students showed a significant increase in resilience and mindfulness, compared to 247 students who did not engage in the intervention [ 35 ]. Mindfulness was sustained at one-year follow up, suggesting positive long-term impacts of the intervention [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the present results, a short-term increase in resilience was found among forty-four participants who engaged in six weekly mind-body intervention sessions [ 34 ]. Similarly, a study found that after engaging in a 9 week mind-body intervention, 279 students showed a significant increase in resilience and mindfulness, compared to 247 students who did not engage in the intervention [ 35 ]. Mindfulness was sustained at one-year follow up, suggesting positive long-term impacts of the intervention [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study found that after engaging in a 9 week mind-body intervention, 279 students showed a significant increase in resilience and mindfulness, compared to 247 students who did not engage in the intervention [ 35 ]. Mindfulness was sustained at one-year follow up, suggesting positive long-term impacts of the intervention [ 35 ]. Contrary to the current findings, an intervention study with 232 medical students during one semester in New Zealand did not find a statistically significant difference between a weekly peer-led mindfulness group and the control group [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative and open-ended comments from the survey suggest that the UAPD Mind-Body Skills Group participants found support among one another while exploring mind-body skills and their potential utility together. This outcome can counter a culture in which residents feel stressed, lonely, and devalued, and it can be a powerful antidote to the forces that contribute to burnout [ 16 ], a theme that appears in the research on the effects of mind-body skills programs on students [ 5 , 11 ]. One cohort of the UAPD Mind-Body Skills Group continued meeting to explore mind-body skills after the conclusion of the course.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications indicate that healthcare institutions have begun to adopt courses and programs that promote resilience in healthcare professionals [6][7][8][9][10][11]. As the body of research on interventions to combat burnout grows, it is important to assess multiple aspects of implementing such courses in addition to measuring effects on burnout.…”
mentioning
confidence: 99%
“…Several undergraduate academic medical programs have proactively implemented student wellness programs and resources for the early prevention of burnout (Slavin, Schindler, and Chibnall, 2014;Drolet and Rodgers, 2010;Bitonte and DeSanto, 2014;Dyrbye, Satele and Shanafelt, 2017;Novak et al, 2020;Bagby-Stone, 2021). As the number and comprehensiveness of wellness initiatives have grown, so have the implementation strategies.…”
Section: Undergraduate Medical Education Wellness Initiativementioning
confidence: 99%